1996
DOI: 10.1128/aem.62.1.133-140.1996
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Substrate Consumption and Enzyme Synthesis in Chelatobacter heintzii during Growth in Carbon-Limited Continuous Culture with Different Mixtures of Glucose and Nitrilotriacetate

Abstract: Regulation of nitrilotriacetate (NTA) degradation and expression of NTA monooxygenase (NTA-MO) in the NTA-degrading strain Chelatobacter heintzii ATCC 29600 in continuous culture at a dilution rate of 0.06 h ؊1 under transient growth conditions when the feed was switched between media containing NTA, glucose, or different mixtures thereof as the sole carbon and energy sources was investigated. A transition from NTA to glucose was accompanied by a rapid loss of NTA-MO. A transition from glucose to NTA resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 48 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…This, however, provides only limited information concerning the regulation processes taking place under conditions found in wastewater treatment plants or in the environment which are characterised by rather low substrate concentrations. Therefore, experiments with C. heintzii ATCC 29600 were conducted in carbon‐limited continuous culture fed with either NTA or glucose to get a better insight in possible regulation mechanisms of NTA breakdown during growth under conditions similar to those found in the environment [236,237].…”
Section: Regulation Of the Apca Degradation And Enzyme Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, provides only limited information concerning the regulation processes taking place under conditions found in wastewater treatment plants or in the environment which are characterised by rather low substrate concentrations. Therefore, experiments with C. heintzii ATCC 29600 were conducted in carbon‐limited continuous culture fed with either NTA or glucose to get a better insight in possible regulation mechanisms of NTA breakdown during growth under conditions similar to those found in the environment [236,237].…”
Section: Regulation Of the Apca Degradation And Enzyme Expressionmentioning
confidence: 99%
“…Consequently, cells have to adapt to the changing conditions, and the lag phase resulting from these adaptation processes can severely affect the efficiency of biodegradation over long time periods [241]. To investigate the dynamic behaviour of NTA degradation in a continuous culture of C. heintzii under transient conditions, the feed was switched from a medium containing glucose only to one containing either NTA only or mixtures of glucose and NTA [237]. When glucose‐pregrown cells were suddenly confronted with NTA as sole source of carbon, nitrogen and energy, a long lag phase of about 25 h was measured until NTA MO expression started.…”
Section: Regulation Of the Apca Degradation And Enzyme Expressionmentioning
confidence: 99%
“…This, however, provides only limited information concerning the regulation processes taking place under conditions found in wastewater treatment plants or in the environment which are characterised by rather low substrate concentrations. Therefore, experiments with C. heintzii ATCC 29600 were conducted in carbon-limited continuous culture fed with either NTA or glucose to get a better insight in possible regulation mechanisms of NTA breakdown during growth under conditions similar to those found in the environment [236,237].…”
Section: Regulation Of Nta Degradationmentioning
confidence: 99%
“…Consequently, cells have to adapt to the changing conditions, and the lag phase resulting from these adaptation processes can severely a¡ect the e¤ciency of biodegradation over long time periods [241]. To investigate the dynamic behaviour of NTA degradation in a continuous culture of C. heintzii under transient conditions, the feed was switched from a medium containing glucose only to one containing either NTA only or mixtures of glucose and NTA [237]. When glucose-pregrown cells were suddenly confronted with NTA as sole source of carbon, nitrogen and energy, a long lag phase of about 25 h was measured until NTA MO expression started.…”
Section: Regulation Of Nta Degradationmentioning
confidence: 99%
“…The growth pattern has been classified into three broad categories: (i) Sequential uptake of the substrates regardless of the pre-fermentor conditions, typically through catabolite repression Venkatesh et al, 1997), (ii) simultaneous uptake of substrates regardless of the pre-fermentor conditions , and (iii) substrate uptake pattern depending on pre-fermentor conditions or adaptation to specific substrates. Several studies in fermentation physiology have revealed that substrate utilization patterns are analogous to the dynamics of the rate limiting enzymes, which are responsible for catalyzing the uptake and catabolism of substrates (Bally and Egli, 1996;Jacob and Monod, 1961). This concept has been used in modeling of microbial growth kinetics and substrate utilization pattern via cybernetic principles (Bapat et al, 2006c;Dhurjati et al, 1985;Kompala et al, 1984;Ramkrishna, 1983;Ramakrishna et al, 1996;Venkatesh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%